Hand-eye / eye-hand / the egg, the fig and the figa - Alcántara Sánchez, María Ángeles (Re-visiones, 2024)
Political history of flowers" by Equipo Jeleton is a series of interventions in graphic, textual and musical repertoires that renegotiate and re-politicize floral symbolism. Some motifs in the chapter-exhibitions have been visuality and passivity, magic and the power to heal, extravagance and sensuality cuir, listening, speaking, reading in the articulate and inarticulate, in the insinuated in the hidden. The floral tarot or florilegium of Jeleton is a deck of cards. The cards summon principles from flowers, bodies and figures. The principles are powers, not the power of the one who has you, but the power of the one you have. The power to see what does not appear. The power to read what is not written. The power to hear what is unsaid. The power to touch what is denied, is present. At the surface of the skin. "Political History of Flowers" proposes an iconological study from the sociology of the image, on the diverse imaginaries of flora. It proposes a deconstructed mythopoiesis, made autohistory and biomythography. A research work on symbolic collective repertoires on the representation of the flower, ranging from the story, to poetry, song, decoration... And an analysis of its diverse public and political facets, of resistance and counter-visulities, translated into diverse languages and readings. Above all, a flower becoming. "Historia Política de las Flores" began in 2003 with the edition of the book "Las lilas de Jeleton", published by Belleza Infinita, Bilbao, continued with the edition of three vinyl singles, a selection of poems set to music from the book and in recent years Jeleton has held a series of drawing exhibitions of the project comprising: "Historia política de las flores, o cuando las lilas se volvieron violetas" (2014), "Historia política de las flores 2: Floripondio" (2015), both in La Taller, Bilbao, "Historia política de las flores 3: Azucenas atigradas" at Halfhouse, Barcelona, "Historia política de las flores 4: No morirá la flor" at the X Bienal Centroamericana, San José de Costa Rica (2016), "Història política de les flors 5: Desflorar" at Ana Mas Projects gallery, Barcelona (2017), "Historia política de las flores 6: Florilegio" (2017) at Tabakalera, San Sebastian, "Historia política de las flores: Floritura" (2017), at La Taller, Bilbao, "El problema con las Flores" (2019) at Centro Párraga, Murcia and "LOREBURU, LOREBEGI: Historia política de las Flores" (2021) at La Taller, Bilbao. For this visual essay we have resorted to the cards of the Jeleton Florilegium tarot, specifically the card "IV: hand" and card "II: The mystical daughter", as a way of integrating a symbolic esoteric narrative about doing: hands to work, and seeing: hand-eye-hand. In order to continue with the representation of the artistic practice agreed and inscribed in our bodies. For this I have selected the choreography made layer extended on two pages, a collaboration with Degénero ediciones (2020), Barcelona, and the drawing-symbol of the obsidian egg inside me, part of the fanzine "Mal Oficio" (2017), made at the Huarte Contemporary Art Center. Jeleton is a working team formed in 1999 by Jesus Arpal Moya or Jesús Jeleton and María de los Ángeles Alcántara or Gelen Jeleton.